An Updated Meta-Analysis Based on the Preclinical Evidence of Mechanism of Aconitine-Induced Cardiotoxicity - Jiang, Hong; Zhang, Yating; Zhang, Yi; Wang, Xiaobo; Meng, Xianli (Frontiers in Pharmacology, 2022)
Background: Most of Aconitum species in traditional Chinese medicine have the effect of dispelling wind, dehumidifying, warming the meridian and relieving pain. Aconitine is the characteristic chemical component with the function of anti-inflammatory, analgesic and heart-strengthening effects. However, improper use will produce cardiotoxicity and neurotoxicity. Currently the mechanisms of cardiotoxicity caused by aconitine are wheels within wheels without been fully disclosed. Systematic review and meta-analysis were therefore conducted to summarize the available evidence of myocardial toxicity caused by aconitine. Methods: We searched PubMed, Embase, Web of Science, National Knowledge Infrastructure, WANFANG and VIP information database for relevant preclinical studies. All the data were analyzed by RevMan version 5.3. Results: Thirty-two studies met final inclusion criteria, including both in vivo and in vitro study types. After aconitine treatment, the heart rate of animals was obviously abnormal, and the morphology and function of myocardial cells were significantly changed. Aconitine can induce changes in the electrophysiological activity of cardiac myocytes by regulating Na+, Ca2+ and K+ currents. Meanwhile, the mechanisms of cardiotoxicity of aconitine may be related to triggering mitochondrial dysfunction by inducing mitochondrial apoptosis and autophagy. It should not be ignored that the overactivation of NLRP3 inflammasome also exacerbates aconitine's cardiotoxicity. Conclusions: Altered ion channels and mitochondrial function, as well the signaling pathways interacting with NLRP3 may deserve further study for aconitine-induced cardiotoxicity.